Fabrication And Characterisation Of Molecularly Doped, Single-Layer Organic Electroluminescent Devices - Yang, Ren Bin (2009)
In this project, organic-molecule based electroluminescent devices, or simply organic light emitting diodes (OLEDs) were spin-coated from solution to form an organic thin film between two electrodes: a semiconducting transparent Indium-tin oxide layer and the aluminium layer.